Role of intraoperative parathyroid hormone in guiding parathyroidectomy - Pereira, Chirag (Acta Biomedica Atenei Parmensis, 2023)
Background and Aim: The aim of the study was to determine the sensitivity, specificity and diagnostic accuracy of intra-operative parathyroid hormone (IOPTH) in patients undergoing surgery for primary hyperparathyroidism based on Miami criteria. Methods: A total of 107 medical records of patients who underwent surgery for primary hyperparathyroidism were reviewed from August 2018 to December 2021. Patients that underwent surgery for recurrent or persistent pHPT were excluded from the study and the following data was analysed: sex, age, pre-operative PTH and 10 minutes post excision PTH levels, type of surgery and histopathological features. Results: There was a greater number of women (79.5%) in the study with a mean age of 65.14 years. The mean preoperative PTH were 17.7 pmol/L while the mean intra-operative PTH following excision was 6.5 pmol/L. The sensitivity, specificity and diagnostic accuracy of intra-operative PTH were 86.14%, 100% and 86.9%, respectively. Conclusion: Intra-operative PTH is a valuable investigation that can guide successful parathyroidectomy.